Poverty, changing political regimes, and social cash transfers in Zimbabwe, 1980 - 2016 - Isaac Chinyoka (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Since 2000, Zimbabwe has been under some pressure to provide more fully for its children. It is not clear whether child poverty has worsened, although AIDS, drought, and economic mismanagement have all compromised poverty reduction. In any case, child poverty has come under increased scrutiny, in part because of the Millennium Development Goals and the growing interest in new kinds of intervention among international agencies and donors. Zimbabwe might have adopted the child-oriented cash transfer programmes or subsidies associated with one or other of the 'models' developed by its richer neighbours to the south (South Africa, Botswana, Namibia). It might also have adopted the models favoured, and promoted energetically, by the World Bank, UNICEF, and other external agencies. But ZANU-PF - which was in power until 2009 and after 2013, and shared power between those dates - resisted cash transfer programmes, favouring instead agricultural interventions (including land reform and farm input subsidy programmes). ZANU-PF's ambivalence towards cash transfer programmes represents political choices informed by the nature of Zimbabwean society and politics.
Keywords: H53; H55; I32; I38; Z18; 330; poverty; child poverty; politics; social cash transfers; social protection; families